Analytical representations for frequency dependences of microwave permeability - Rozanov, K. N.; Koledintseva, M. Y. (2012 IEEE International Symposium on Electromagnetic Compatibility, 2012)
Electromagnetic materials applied to solve various EMC and EMI problems require adequate analytical description of their RF and microwave material parameters. This is necessary for numerical optimization of wideband electromagnetic performance of devices incorporating these materials. The paper discusses the shape of frequency dependences of microwave permeability in homogeneous materials and composites. The Lorentzian frequency dispersion law is shown to allow for rather accurate description of all types of magnetic loss peaks, including those related to the ferromagnetic resonance and the effect of eddy currents. To model wideband electromagnetic performance of composites, mixing laws are typically used. The problem is which mixing law is to be chosen to adequately describe a particular composite. The paper gives recommendations on how to make the choice of a proper mixing rule.